Human Resources Training and Development at Mitra Packindo Machinery Surabaya - Kristanto Abraham Rini; Leonard Adrie Manafe (CV ODIS, 2022)
This study describes human resources (HR) development and training at Mitra Packindo Machinery Surabaya. The research uses qualitative methods using data collection techniques in observations and interviews with informants. The author determines the purposive sampling technique to examine informants within the company. The informants who attended this study were one person in the Supervisor position, one person in the Digital Sales position, one person in the OM (advertising and promotion) section, one person filling the Operator position, and two people in the Warehouse Staff section. Researchers involve the triangulation strategy to test the legitimacy of the information. The results of the review show that the strategy used is proven to be feasible for educating, for example, the interaction of preparation for future workers using learning techniques within the scope of the organization and direct training, while in the representative development process, the technique used by Mitra Packindo Machinery is the job rotation method, basic for substitution and further reuse of research methods